Vineyard weed community dynamics in the Dão winegrowing region - Monteiro, Ana (2012)
With the aim of analysing the influence of both the sub-region and weed-control practices on vegetation composition and dynamics in the Portuguese Dão Winegrowing Region, 120 vineyards were surveyed for weeds and winegrowers were asked to respond to a questionnaire in 2008. 206 taxa distributed across 31 families were recorded, with a predominance of Fabaceae, Asteraceae and Poaceae. The predominant vineyard inter-row soil management techniques were cover cropping (53%), with some cover sown but mostly relying on resident vegetation, and soil tillage (31%). Herbicides were applied in the row in 46%, and in the overall area in 4%, of the vineyards. Canonical correspondence analysis revealed signifi cant effects of the sub-region and the different soil management strategies on vineyard community structure. Compared with the last (and only) study, which took place in 1950, weed composition was different and species diversity increased. The present study showed that resident vegetation also increased plant diversity. The dynamics of the perennial weed species Cynodon dactylon and Convolvulus arvensis must be carefully evaluated in order to avoid severe competition with the vine.